The Influence Of Brand Image, Product Quality, And Price Perception On The Purchase Decision Of Jims Honey Products Among Students In Pekanbaru - Azahra, Desti Putri; Rachmad, Ferizal (InJEBA : International Journal of Economics, Business and Accounting, 2025)
This study aims to examine the influence of brand image, product quality, and price perception on the purchasing decisions of Jims Honey products among students in Pekanbaru. Data collection was conducted using a questionnaire. The population in this study consists of students in Pekanbaru. A sample of 100 respondents was selected using purposive sampling. The data analysis employed a quantitative approach with multiple linear regression. The results of the simultaneous test show that brand image, product quality, and price perception collectively influence the purchasing decisions of Jims Honey products among students in Pekanbaru. Furthermore, the partial tests revealed that brand image, product quality, and price perception each have a significant effect on purchasing decisions. The R square value obtained was 0.657 or 65.7%, while the remaining 34.3% is influenced by other variables not included in this study.